Infective Endocarditis in a ?-thalassemia Major Child (Cardiovascular Journal, 2015)
Almost all patients who develop infective endocarditis (IE) had history of congenital or acquired heart disease.We report a 9 years old boy who was diagnosed as ?-thalassemia major since age 1.5 years, admitted to hospital with chief complaint of difficulty of breathing for 1 week before admission, accompanied by fever. Holosystolic murmur of grade 3/6 was found in the lower left sternal border along with hepatosplenomegaly. Chest x-ray depicted right ventricle enlargement and opaque densities in the middle field of left lung. Blood culture showed growth of Staphylococcus aureus. Echocardiography detected thickening tricuspid valve with oscillating mass in the tricuspid valve, severe pulmonary hypertension, and minimal pericardial effusion. Diagnosis of IE was made. After clinical improvement he was discharged with good condition. The diagnosis of IE in children without heart defects is difficult to establish and right-sided IE is rare in children that a high suspicion index should be considered. DOI: http://dx.doi.org/10.3329/cardio.v7i2.22263 Cardiovasc. j. 2015; 7(2): 145-149